Determining The Factors to Increase Buying Decisions Among Fashion Distro Consumers - Luthfi Jauharin Abdillah; Rosana Eri Puspita (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study aims to determine the effect of product design, brand image, and religiosity on purchasing decisions. This study uses a quantitative method by processing primary data through a questionnaire (questionnaire) given to people who understand distro fashion with the brand name is Maternal Disaster. The sample of this study was 96 respondents with a purposive random sampling technique. The data obtained were then processed using the SPSS 20 analysis tool. The results showed that product design had no effect on purchase intention, brand image and religiosity had an effect on purchase intention. Product design, brand image influence purchasing decisions, while religiosity doesn't affect purchasing decisions. Brand image and religiosity have a significant effect on purchasing decisions through purchase intention, and product design has no significant effect on purchasing decisions through purchase intention.